Digital Learning Practices and Their Influence on Employees’ Job Performance in Manufacturing Industry at Chennai - Devanathan. D; Dr. Raja Manickam. E (Revista Electronica de Veterinaria, 2024)
In the rapidly evolving manufacturing industry, digital learning practices have become an essential component for enhancing employees’ skills and performance. With increasing adoption of digital technologies, organizations are focusing on providing accessible and flexible learning opportunities to improve workforce efficiency. This study examines the influence of digital learning practices on employees’ job performance in the manufacturing industry at Chennai. The study considers access to digital learning resources and self-paced learning ability as independent variables, and quality of work and time management as dependent variables.Primary data were collected from 55 employees working in the manufacturing sector using a structured questionnaire based on a five-point Likert scale. Descriptive statistics, Pearson correlation analysis, and regression analysis were employed to examine employees’ opinions and to analyze the relationship between digital learning practices and job performance variables. The results reveal that access to digital learning resources and self-paced learning ability have a significant positive influence on employees’ quality of work and time management.The findings indicate that employees who have better access to digital learning materials and the ability to learn at their own pace demonstrate improved work quality and effective time management. The study highlights the importance of providing adequate digital learning resources and promoting self-directed learning among employees to enhance their performance.The study provides valuable insights for manufacturing organizations to design effective digital learning strategies that improve employees’ work efficiency and overall organizational performance.